2011
DOI: 10.1103/physrevc.84.015212
|View full text |Cite
|
Sign up to set email alerts
|

Polarization effects in elastic proton-electron scattering

Abstract: The experimental observables for the elastic reaction induced by protons scattering from electrons are calculated in the Born approximation. The differential cross section and polarization observables have been derived assuming one photon exchange. Numerical estimates are given for spin correlation coefficients, polarization transfer coefficients and depolarization coefficients in a wide kinematical range. Specific attention is given to the kinematical conditions; that is, to the specific range of incident ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Usual special reference frames have been chosen for the consideration of specific polarization observables. More recently, Gakh et al [10] have studied polarization effects in elastic protonelectron scattering, which on a formal basis is equivalent to electron-proton scattering. They have considered three types of polarization observables: outgoing proton polarization transferred either from a polarized target electron or from an incoming polarized proton, and the beam target asymmetry from polarized beam and target.…”
Section: Introductionmentioning
confidence: 99%
“…Usual special reference frames have been chosen for the consideration of specific polarization observables. More recently, Gakh et al [10] have studied polarization effects in elastic protonelectron scattering, which on a formal basis is equivalent to electron-proton scattering. They have considered three types of polarization observables: outgoing proton polarization transferred either from a polarized target electron or from an incoming polarized proton, and the beam target asymmetry from polarized beam and target.…”
Section: Introductionmentioning
confidence: 99%
“…[5] it was shown that polarization observables are very small at small energy, making very difficult their measurement. Therefore, the application of the polarization method [12] to inverse kinematics seems very challenging at low energy.…”
mentioning
confidence: 99%
“…[5]. It has been shown that for a given energy of the proton beam, the maximum value of the four-momentum transfer squared is:…”
mentioning
confidence: 99%
“…But the lepton mass cannot always be neglected: besides the present case, where the energy is of the order of the muon mass, the terms related to the lepton mass have a large effect at high energies in case of inverse kinematics as proton-electron scattering, which is object of Ref. [25], as well as in the crossed channel, the antiproton annihilation into a lepton pair [26]) o f interest for the antiproton annihilation experiment at the GSI Facility for Antiproton and Ion Research (PANDA at FAIR). In this respect, the subject of the present paper is relevant to other elementary processes.…”
Section: Discussionmentioning
confidence: 98%
“…Besides the change in the kinematical variables, this is due to the presence of k\ in the denominator of Eq. (25) and to the additional terms accompanying the structure functions [see Eqs. (27) and (29)].…”
Section: B Parametrization Of Deuteron Form Factorsmentioning
confidence: 99%